Records of breeding in Wilson’s Plover Charadrius wilsonia with new localities for Brazil - Andrade,L. P. (2020)
Abstract Wilson’s Plover, Charadrius wilsonia, is widely distributed in coastal areas of the Americas. This report presents the first record of breeding in this species on Coroa do Avião Island, on the coast of Pernambuco, and in the estuary of the Cardoso and Camurupim rivers, on the coast of Piauí, in northeastern Brazil, extending the known area of reproduction of this species in this region. One breeding pair was observed on October 29th 2014 on Coroa do Avião Island, and a second pair was recorded on April 6th 2016 in the Cardoso/Camurupim estuary on the Piauí coast. Both the male and the female contributed to the incubation of the eggs. The nest on Coroa do Avião island was camouflaged by the local vegetation, but despite this, the eggs were attacked by a predator. Possible predators observed on the island included Caracara plancus and domestic cats and dogs.